Pengaruh Return On Asset, Beban Operasional Pendapatan Operasional, dan Produk Domestik Bruto Terhadap Pangsa Pasar Industri Keuangan Non-Bank Syariah di Indonesia - Fatoni, Ahmad; Az Zahra, Annisa Yaspa; Utami, Kurnia Dwi Sari (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to determine the effect of Return On Asset (ROA), Operating Expenses on Operating Income (BOPO), and Gross Domestic Product (GDP) on the Market Share of the Islamic Non-Bank Financial Industry (IKNB) in Indonesia. This research was tested using E-Views 12. This research uses a quantitative approach and the research data is secondary. The results of this study indicate that partially, Operating Expenses on Operating Income (BOPO) and Gross Domestic Product (GDP) have a significant effect on the Market Share of the Islamic Non-Bank Financial Industry (IKNB). However, Return On Asset (ROA) has no significant effect on the Market Share of the Islamic Non-Bank Financial Industry (IKNB). While simultaneously, Return On Asset (ROA), Operating Expenses on Operating Income (BOPO), and Gross Domestic Product (GDP) have a significant effect on the Market Share of the Islamic Non-Bank Financial Industry (IKNB) in Indonesia.